Spread and change in stress resistance of Shiga toxin‐producing Escherichia coli O157 on fungal colonies. Issue 6 (6th August 2013) - Lee, Ken‐ichi; Kobayashi, Naoki; Watanabe, Maiko; Sugita‐Konishi, Yoshiko; Tsubone, Hirokazu; Kumagai, Susumu; Hara‐Kudo, Yukiko
Summary To elucidate the effect of fungal hyphae on the behaviour of Shiga toxin‐producing Escherichia coli (STEC) O157, the spread and change in stress resistance of the bacterium were evaluated after coculture with 11 species of food‐related fungi including fermentation starters. Spread distances of STEC O157 varied depending on the co‐cultured fungal species, and the motile bacterial strain spread for longer distances than the non‐motile strain. The population of STEC O157 increased when co‐cultured on colonies of nine fungal species but decreased on colonies of Emericella nidulans and Aspergillus ochraceus. Confocal scanning microscopy visualization of green fluorescent protein‐tagged STEC O157 on fungal hyphae revealed that the bacterium colonized in the water film that existed on and between hyphae. To investigate the physiological changes in STEC O157 caused by co‐culturing with fungi, the bacterium was harvested after 7 days of co‐culturing and tested for acid resistance. After co‐culture with eight fungal species, STEC O157 showed greater acid resistance compared to those cultured without fungi. Our results indicate that fungal hyphae can spread the contamination of STEC O157 and can also enhance the stress resistance of the bacteria.